156k views
4 votes
Use the substitution method to solve the system of equations.3x + 2y = 13y = x - 1O A. (2,1)O B. (2,3)O C. (3,2)O D. (1,2)

User Kovshenin
by
5.1k points

1 Answer

6 votes

3x + 2y = 13

y = x - 1

We want to substitute the second equation into the first equation.

In the first equation, everytime we see "y" substitute x-1

3x +2y = 13

3x + 2( x-1) = 13

Distribute

3x +2x -2 = 13

Combine like terms

5x -2 = 13

Add 2 to each side

5x-2+2 = 13+2

5x = 15

Divide each side by 5

5x/5 = 15/5

x = 3

Noe we can find the value of y by using the second equation

y = x-1

y = 3-1

y =2

The solution is

( 3,2)

User JustWork
by
4.5k points